2015
DOI: 10.1016/j.jmaa.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Random continued fractions: Lévy constant and Chernoff-type estimate

Abstract: Abstract. Given a stochastic process {An, n ≥ 1} taking values in natural numbers, the random continued fractions is defined as [A 1 , A 2 , · · · , An, · · · ] analogue to the continued fraction expansion of real numbers. Assume that {An, n ≥ 1} is ergodic and the expectation E(log A 1 ) < ∞, we give a Lévy-type metric theorem which covers that of real case presented by Lévy in 1929. Moreover, a corresponding Chernoff-type estimate is obtained under the conditions {An, n ≥ 1} is ψ-mixing and for each 0 < t < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Theorem 3.9 (cf. Theorem 2 in [14] or Theorem B in [49]). For any δ > 0, there exist N > 0, B > 0, α > 0 such that for all n ≥ N ,…”
Section: Gauss Map: Tmentioning
confidence: 99%
“…Theorem 3.9 (cf. Theorem 2 in [14] or Theorem B in [49]). For any δ > 0, there exist N > 0, B > 0, α > 0 such that for all n ≥ N ,…”
Section: Gauss Map: Tmentioning
confidence: 99%
“…A natural question is arisen: what are the rates of these decreasing probabilities? In fact, Fang et al [8] have considered these decays and showed that the upper bounds of these decays are exponential. In this paper, we not only obtain the upper and lower bounds of these decreasing probabilities, but also give them explicit formulae.…”
Section: Theorem 11 ([14]mentioning
confidence: 99%
“…, a m+n in the periodic part of expansion (3). Many results on the Lévy constant have been studied by some authors, see [2,[6][7][8][9]. Some other limit theorems of {q n (x), n ≥ 1} in the continued fraction expansion of real numbers have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%